USEFULNESS OF RAJYOGA MEDITATION IN ASSESSMENT OF GENERAL WELL BEING OF BADMINTON PLAYERS AN EXPERIMENTAL STUDY - KOMAL MESHRAM; AJAY MESHRAM (International Journal of Pharma and Bio Sciences, 2016)
Mental health and physical health are very closely tied together, and each can exert a significant impact on other. Meditation technique is normally used in sports for the purpose of upgrading the rate of recovery after exercise or enhancing performance by improving the handling of anxiety pressure. The present study was undertaken to assess the general well being of badminton players before and after Rajyoga meditation. 30 healthy male badminton players (18-25 years old) playing at district level were randomly selected and recruited purely on voluntary basis. General well being was assessed by using WHO-QOL health questionnaire before and after giving Rajyoga meditation. Student’s paired‘t’ test was used. Four domains of WHO QOL health questionnaire were assessed before and after Rajyoga meditation. Significant improvement in general well being was seen after Rajyoga meditation. Improvement in results was reflected as increase in self confidence and positivity in badminton players.